The Relationship Between Learning Style and Critical Thinking Skills in Learning Kinetic Theory of Gases - Dedi Riyan Rizaldi; Muh. Makhrus; Ziadatul Fatimah; Chester Ian Sotto Pineda (Journal of Science and Science Education, 2021)
This study aims to determine the relationship between learning styles and critical thinking skills in learning gas kinetic theory. This type of research is pre-experimental with a level 3 factorial design that uses three classes to be sampled, namely XI IPA 1, XI IPA 2, and XI IPA 3 in SMAN 7 Mataram. The learning style data collection technique used a questionnaire, while the critical thinking skill data used a multiple-choice test and description. The data obtained were analyzed using two-way ANOVA assisted by IBM SPSS Statistics 21. Based on the analysis obtained an F value of 0.03 <0.05, which illustrates a relationship between learning styles and students' critical thinking skills on learning kinetic theory of gases.